The effects of fine-needle biopsy on thyroid hormone levels - Alpay, H. Cengiz; Kalidag, Turgut; Keles, Erol; Kaygusuz, Irfan; Yalcin, Sinasi; Kapusuz, Zeliha (Sage Publications Ltd, 2007)
Objective: Our study aim was to investigate the effects of fine-needle biopsy used for thyroid nodules on serum thyroid hormone levels. Study Design: A total of 25 patients who had solid nodules of the thyroid gland and normal thyroid hormone levels underwent diagnostic fine-needle biopsy for a nodule of the thyroid gland. Methods: Venous blood samples were drawn from the cases for measurement of serum total T-3 and T-4, free T-3 and T-4, thyroid-stimulating hormone, and thyroglobulin levels before, immediately after, and 30 minutes after the initial biopsy. Results: Total T3 and thyroglobulin levels were found to be significantly higher immediately and 30 minutes following fine-needle aspiration biopsy, compared to the baseline levels (P < 0.05). Conclusion: Prelminary data suggest that thryoid hormone levels show a mean increase of about 20% immediately after fine-needle aspiration. Significance: The implication of this finding on patient care should be determined on an individual basis. (C) 2007 American Academy of Otolaryngology-Head and Neck Surgery Foundation. All rights reserved.
Keywords: Aspiration Biopsy; Nodules